Synthesis and Characterization of N-(N-Methylene-3H/alkyl-2,6-diphenyl piperiden-4-ol) dibenzyl amines - RADHAMANI, R.; RAKKIYAPPAN, P.; JAMBULINGAM, M.; KIRUTHIKA, J.; SATHISH, ASHA; KARTHIKEYAN, S. (Asian Journal of Chemistry, 2010)
Various 2,6-diphenyl-4-piperidones (1a-d) prepared through Mannich reaction by the condensation of benzaldehyde with different appropriate ketones and dry ammonium acetate, on addition of formaldehyde and dibenzylamine in the presence of ammonium chloride, afford the novel Mannich bases of N-(N-methylene-2,6- diphenyl-3-H/alkyl piperiden-4-o1)dibenzyI amines (2a-d). The structures of all the compounds have been confirmed on the basis of their analytical, JR, 1H NMR and mass spectral data.